2023
DOI: 10.1101/2023.11.29.568318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aβ Amyloid Scaffolds the Accumulation of Matrisome and Additional Proteins in Alzheimer’s Disease

Yona Levites,
Eric B. Dammer,
Yong Ran
et al.

Abstract: We report a highly significant correlation between human Alzheimer’s disease (AD) brain proteome changes and those in CRND8 APP695NL/F transgenic mice. Comparing protein changes observed in the CRND8 mice with co-expression networks derived from human Alzheimer’s disease (AD), reveals both conserved and divergent module changes. Many proteins in the most highly conserved module (M42, matrisome) accumulate in plaques, cerebrovascular amyloid (CAA), dystrophic neuronal processes, or a combination thereof. Overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 137 publications
1
6
0
Order By: Relevance
“…These proteins either directly bind to amyloid or are associated with amyloid plaques, highlighting their crucial connection to amyloid deposition in the brain. 23,48 As expected, MAPT was not uniquely altered in AD but showed higher elevation in AD than PSP, reflecting higher burden of tau pathology in frontal cortex in AD cases. The remaining signature of increased proteins in AD was associated with nuclear metabolism (SDC4, SPOCK3, CEP63) Two-color heatmap represents strength of positive (red) or negative (blue) correlation, with p values provided for all correlations with p < 0.05.…”
Section: Correlation Of Cerebrovascular Proteomic Modules With Distin...supporting
confidence: 61%
“…These proteins either directly bind to amyloid or are associated with amyloid plaques, highlighting their crucial connection to amyloid deposition in the brain. 23,48 As expected, MAPT was not uniquely altered in AD but showed higher elevation in AD than PSP, reflecting higher burden of tau pathology in frontal cortex in AD cases. The remaining signature of increased proteins in AD was associated with nuclear metabolism (SDC4, SPOCK3, CEP63) Two-color heatmap represents strength of positive (red) or negative (blue) correlation, with p values provided for all correlations with p < 0.05.…”
Section: Correlation Of Cerebrovascular Proteomic Modules With Distin...supporting
confidence: 61%
“…This protein signature, previously mapped to a bulk Brodmann area 9 “Matrisome” module 29 , has been shown to consistently distinguish AD from other proteinopathies. These proteins either directly bind to amyloid or are associated with amyloid plaques, highlighting their crucial connection to amyloid deposition in the brain 29,33 . As expected, MAPT was not uniquely altered in AD but showed higher elevation in AD than PSP, reflecting higher burden of tau pathology in frontal cortex in AD cases.…”
Section: Resultsmentioning
confidence: 99%
“…This pattern was evident in both bulk and vascular proteomes. Several members of the matrisome module, including SMOC1, MDK, NTN1 have been previously shown to bind Aβ and co-localize with amyloid plaques in AD brains 29,49 and in a mouse model of AD amyloidosis 31,33 . In the current study, beyond the core proteins that are central to the module’s function, we have identified novel markers-SMOC2, ITM2C, HGF, CHADL, and others- that were not discernible at the bulk level using similar database search algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this evidence of concordance of pathological changes across species based on our and recent proteomics studies 73 , despite evident inter-species differences between humans and mice, we focused our analysis to canonical transcriptomic markers (Supplementary Data 4) of different neuronal classes 49 , and identified distinct patterns of change of neuronal proteins with aging and genotype (5xFAD vs WT), as well as biological interaction between aging and genotype. Excitatory neuronal proteins (Camk2a, Slc17a7) showed an age-dependent decrease without an impact of genotype.…”
Section: Neuron-specific Molecular Signatures Resolve Vulnerability O...mentioning
confidence: 99%